Ethics and military strategy in the 21st century moving beyond Clausewitz - Lucas, George R. (War, conflict and ethics, 2020)
"This book examines the importance of 'military ethics' in the formulation and conduct of contemporary military strategy. Clausewitz's original analysis of war relegated ethics to the side-lines in favour of political realism, interpreting the proper use of military power solely to further the political goals of the state, whatever those may be. This book demonstrates how such single-minded focus no longer suffices to secure the interest of states, for whom the nature of warfare has evolved to favour strategies that hold combatants themselves to the highest moral and professional standards in their conduct of hostilities. Waging war has thus been transformed in a manner that moves beyond Clausewitz's original conception, rendering political success wholly dependent upon the cultivation and exercise of discerning moral judgment by strategists and combatants in the field. This book utilises a number of perspectives and case studies to demonstrate how ethics now plays a central role in strategy in modern armed conflict. This book will be of much interest to students of just war, ethics, military strategy, and international relations."--Provided by publisher